Reflector-Based Digital Beam-Forming Radar System for Space Debris Detection - Patyuchenko, Anton; Marwan, Younis; Krieger, Gerhard (International Radar Symposium (IRS), 2010)
The paper considers a novel radar system concept for space debris detection based on a reflector antenna and utilizing digital beam-forming techniques. The main operational principles of the system are discussed. First, a classical radar system and its performance aspects are considered. Then in terms of the considered aspects, the performance enhancements of the novel digital beam-forming radar are demonstrated.
DLR Import::2019-04-03